2014
DOI: 10.1128/iai.01140-13
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3-Deficient Mice Have Increased Resistance to Blood-Stage Malaria

Abstract: The contribution of interleukin-3 (IL-3), a hematopoietic growth factor and immunoregulatory cytokine, to resistance to bloodstage malaria was investigated by infecting IL-3-deficient (knockout [KO]) mice with Plasmodium berghei NK65. Male IL-3 KO mice, but not female mice, were more resistant to infection than wild-type (WT) mice, as evidenced by lower peak parasitemia and prolonged survival. Both male and female IL-3 KO mice had increased splenomegaly and were more anemic than corresponding WT mice. Anemia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…Differential analysis of individual transcriptomics, metabolomics, and lipidomics datasets showed significant alterations of transcriptional and metabolic programs related to inflammation and immune regulation during acute infections that are consistent with a number of reported observations (Auclair et al, 2014; Haque et al, 2001; Sarangi et al, 2014; Sinha et al, 2010; Zago et al, 2012). Altered pathways were related to two axes of immune regulation: those modulating cell proliferation through the cell cycle and those controlling immune function (including cellular immunity).…”
Section: Discussionsupporting
confidence: 89%
“…Differential analysis of individual transcriptomics, metabolomics, and lipidomics datasets showed significant alterations of transcriptional and metabolic programs related to inflammation and immune regulation during acute infections that are consistent with a number of reported observations (Auclair et al, 2014; Haque et al, 2001; Sarangi et al, 2014; Sinha et al, 2010; Zago et al, 2012). Altered pathways were related to two axes of immune regulation: those modulating cell proliferation through the cell cycle and those controlling immune function (including cellular immunity).…”
Section: Discussionsupporting
confidence: 89%
“…Instead, these mice were found to have defects in delayed-type hypersensitivity (3) and in immunity to parasites (4). More recent studies have shown that IL-3 has a detrimental role in experimental autoimmune encephalitis and myocarditis (2, 5), lupus nephritis (6), sepsis (7), and blood-stage malaria (8) and a beneficial role in anti-tick immunity (9).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to bacterial sepsis, in which IRA B cells are reported to either promote (via IL-3) or protect (via GM-CSF) the host, a lack of GM-CSF or IL-3 has opposite outcomes during malaria infection, with GM-CSF-deficient mice exhibiting lower resistance to chronic P. chabaudi infection (19), while IL-3-deficient mice resisted better P. bergheiinduced experimental cerebral malaria (ECM) (20). IRA B cell-derived GM-CSF increases resistance to bacterial sepsis through secreted IgM and subsequent activation of innate myeloid cell phagocytic capacity and bacterial clearance.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the production of GM-CSF by the B1 B cell plasmablasts is partially dependent on both cell-extrinsic type I (IFN-␣/␤) and cell-intrinsic type II (IFN-␥) interferon signaling but is independent of MyD88 signaling, a key cytosolic adaptor of most TLR signaling. Given that GM-CSF and IL-3 are reported to play opposite roles in malaria infection outcomes in mouse models (19,20), we speculate that GM-CSF and IL-3 from these subsets of B1 B cell plasmablasts could represent important contributors to clinical malaria in humans.…”
mentioning
confidence: 90%
See 1 more Smart Citation